The Influence of Sustainability Marketing, Corporate Social Responsibility, Ethical Branding, and Green Consumerism on Brand Equity and Market Position in the Fashion Industry - Permana, Dudi; Ekowati, Dhiana (International Journal of Business, Law, and Education, 2024)
In an effort to break into foreign markets, this study looks into how brand equity and market position are affected by sustainability marketing, corporate social responsibility (CSR), ethical branding, and green consumerism in the Indonesian fashion sector. Data obtained from 197 Indonesian fashion customers was subjected to a quantitative analysis. The associations between the variables were examined using Partial Least Squares (PLS) 3 and structural equation modeling (SEM). The findings show a strong positive correlation between brand equity and market position and sustainability-related criteria (green consumerism, CSR, sustainability marketing, and ethical branding). The results highlight how crucial sustainability and ethical branding are from a strategic standpoint for Indonesian fashion firms looking to gain a competitive edge and become more visible in the international fashion scene.